The critical behavior of 3D Ising spin glass models: universality and scaling corrections - Hasenbusch, Martin; Pelissetto, Andrea; Vicari, Ettore (Journal of statistical mechanics: theory and experiment, 2008)
We perform high-statistics Monte Carlo simulations of three three-dimensional Ising spin glass models: the ± J Ising model for two values of the disorder parameter p, p = 1/2 and 0.7, and the bond-diluted ± J model for bond-occupation probability pb = 0.45. A finite-size scaling analysis of the quartic cumulants at the critical point shows conclusively that these models belong to the same universality class and allows us to estimate the scaling-correction exponent ω related to the leading irrelevant operator, ω = 1.0(1). We also determine the critical exponents ν and η. Taking into account the scaling corrections, we obtain ν = 2.53(8) and η = −0.384(9).
Gesehen am 09.09.2022